Participatory Based Waste Management In The Faculty Of Medicine And Health Sciences Of Alauddin State Islamic University Of Makassar - Firdah Firdah; Andi Susilawaty; Abdul Majid HR. Lagu (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2019)
Waste management has become a pressing issue in many major cities in the world, including in Indonesia. As the health aspect of a faculty is crucial and impacts each member, this research aims to conduct and analysis on the participatory waste management in Faculty of Medicine and Health Sciences of Alauddin State Islamic University of Makassar by addressing the knowledge, attitude and behaviour of students regarding waste management. It uses qualitative method and community-based research (CBR) approach to understand the issue. The samples consist of 150 respondents who are selected by using random sampling technique. The research findings suggest that respondents’ average score on waste management knowledge improves after receiving an intervention, from 77.26 to 86.30. Next, respondents’ average score on their attitude toward waste management also improves after receiving an intervention, from 47.64 to 69.50. They exhibit appropriate response to proper waste management. The findings indicate that students’ knowledge influences their attitude toward waste management issue. The better their knowledge on the issue is the better their displayed attitude becomes, as indicated by the increase in respondents’ average score from 17.25 to 21.84. The significance values of 0.000 p=(<0,05) suggests that there is a significant difference in respondents’ knowledge, attitude and behaviour after an intervention. Thus, this research encourages students and other faculty members to improve their participation in waste management program. Keywords: knowledge, attitude and behavior, management, waste, environment